Improving rice blast resistance of Feng39S through molecular marker-assisted backcrossing - Yang, Dabing; Tang, Jianhao; Yang, Di; Chen, Ying; Ali, Jauhar; Mou, Tongmin (Springer, 2019)
Rice blast caused by Magnaporthe oryzae is one of the most widespread biotic constraints that threaten rice production. Using major resistance genes for rice blast resistance improvement is considered to be an efficient and technically feasible approach to achieve optimal grain yield. Results We report here the introgression of the broad-spectrum blast resistance gene Pi2 into the genetic background of an elite PTGMS line, Feng39S, for enhancing it and its derived hybrid blast resistance through marker-assisted backcrossing (MABC) coupled with genomics-based background selection. Two PTGMS lines, designated as DB16206–34 and DB16206–38, stacking homozygous Pi2 were selected, and their genetic background had recurrent parent genome recovery of 99.67% detected by the SNP array RICE6K. DB16206–34 and DB16206–38 had high resistance frequency, with an average of 94.7%, when infected with 57 blast isolates over 2 years, and the resistance frequency of their derived hybrids ranged from 68.2% to 95.5% under inoculation of 22 blast isolates. The evaluation of results under natural blast epidemic field conditions showed that the selected PTGMS lines and their derived hybrids were resistant against leaf and neck blast. The characterizations of the critical temperature point of fertility-sterility alternation of the selected PTGMS lines, yield, main agronomic traits, and rice quality of the selected PTGMS lines and their hybrids were identical to those of the recurrent parent and its hybrids. DB16206–34/9311 or DB16206–38/9311 can be used as a blast-resistant version to replace the popular hybrid Fengliangyou 4. Likewise, DB16206–34/FXH No.1 or DB16206–38/FXH No.1 can also be used as a blast-resistant version to replace another popular hybrid Fengliangyou Xiang 1. Our evaluation is the first successful case to apply MABC with genomics-based background selection to improve the blast resistance of PTGMS lines for two-line hybrid rice breeding.